Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1037/0022-3514.58.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Person-environment intersections: Everyday settings and common trait dimensions.

Abstract: We thank Nora Hutsko and Jennifer Ryan for their help with Study 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…For example, leadership was more applicable at work than at home and the capacity to love and be loved was more applicable at home. This result is in line with previous research stipulating that situations differ in their suitability for the expression of certain traits (Ten Berge and De Raad 1999;Kenrick et al 1990). …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For example, leadership was more applicable at work than at home and the capacity to love and be loved was more applicable at home. This result is in line with previous research stipulating that situations differ in their suitability for the expression of certain traits (Ten Berge and De Raad 1999;Kenrick et al 1990). …”
Section: Discussionsupporting
confidence: 82%
“…Kenrick et al (1990) found that some traits could be observed across more situations than others. This was found for character strengths as well; bravery and religiousness were the strengths least often applicable, and honesty and social intelligence were the ones most often applicable with the rest of the strengths ranging in between.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, two studies showing that religious settings require a high degree of self-control and involve strong public approval and disapproval for appropriate and inappropriate forms of behavior (Kenrick, McCreath, Govern, King, & Bordin, 1990;Price & Bouffard, 1974) suggest that public religious involvement may influence self-regulation through chronic contact with moralistic, evaluative audiences. Finally, two experiments show that awareness of one's religious shortcomings (i.e., discrepancies between one's religious goals and one's actual religious behavior) leads to a redoubling of religious goal-directed effort (Wenger, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to other social settings (e.g., parks, streets, and even places of work), relatively few behaviors are appropriate in religious settings. Indeed, in one study, U.S. undergraduate psychology students reported that among six relatively comprehensive personality dimensions (i.e., adjustment, likeability, self-control, social inclination, intellectance, and dominance), self-control is the most appropriate trait to express in religious settings (Kenrick, McCreath, Govern, King, & Bordin, 1990). Price and Bouffard (1974) also found that among 15 common settings in which students find themselves (e.g., church, job interviews, movies, restrooms, dorm lounges, and their own rooms), "church" was the setting in which 15 behaviors (e.g., eating, talking, laughing, writing, and crying) were judged by U.S. university students to be, on average, least appropriate (one's own room was the setting in which the 15 behaviors were judged to be most appropriate).…”
Section: Proposition 3b: Religious Communities As Moralistic Audiencmentioning
confidence: 99%
See 1 more Smart Citation